The Policy Formulation Determination Process in Effort to Give Health Services to Society in Saiful Anwar Hospital Malang - Ahmad Sofwani (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
As in many developing countries, public services in education, health, public transportation, housing, social welfare, nutrient, electricity, and drinking water, are carried out by governmental bureaucracy that aims at improving the social welfare of the people. Because of that access to decision making process that determine the public services allocation and access to bureaucracy that determine the services distribution become important in reaching the services even distribution. Access can be used as framework to measure the governmental organizations in reaching the development goals and their abilities to decrease the social imbalances in the society. The research aimed at describing, analyzing and interpreting aspects that related with the policy formulation determination in effort to give health services to society at Syaiful Anwar Hospital, Malang. Based on the scope and reality that want to be investigated in the perspective of health services policy formulation that tend to be approached phenomenologically, then the research used qualitative approach. The results were the determination process of services policy formulation at Syaiful Anwar Hospital, Malang through stages and steps that begun with agenda determination stage, solution alternative identification, solution determination, trial run, evaluation stage, model determination stage, and socialization stage. In agenda determination stage, RSSA leadership take steps: list what agendas that should be considered, determining the agenda priority, and sort the agendas that will be discussed.Keywords: Determination process, policy formulation, public services